2016
DOI: 10.1371/journal.ppat.1005909
|View full text |Cite
|
Sign up to set email alerts
|

Acute Malaria Induces PD1+CTLA4+ Effector T Cells with Cell-Extrinsic Suppressor Function

Abstract: In acute Plasmodium falciparum (P. falciparum) malaria, the pro- and anti-inflammatory immune pathways must be delicately balanced so that the parasitemia is controlled without inducing immunopathology. An important mechanism to fine-tune T cell responses in the periphery is the induction of coinhibitory receptors such as CTLA4 and PD1. However, their role in acute infections such as P. falciparum malaria remains poorly understood. To test whether coinhibitory receptors modulate CD4+ T cell functions in malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 67 publications
5
65
0
Order By: Relevance
“…It would be interesting to investigate if this was due to a low amount of activated T lymphocytes. Other studies of the immune response to P. falciparum acute infections in humans and to P. berghei ANKA infections in mice reported increases in CTLA‐4 expression in activated T lymphocytes. In mononuclear cells isolated from cord blood of women with P. falciparum placental malaria, an increase in antigen‐specific CD4 + regulatory cells CD4 + CD25 + CTLA‐4 + with suppressive characteristics was observed .…”
Section: Discussionmentioning
confidence: 93%
“…It would be interesting to investigate if this was due to a low amount of activated T lymphocytes. Other studies of the immune response to P. falciparum acute infections in humans and to P. berghei ANKA infections in mice reported increases in CTLA‐4 expression in activated T lymphocytes. In mononuclear cells isolated from cord blood of women with P. falciparum placental malaria, an increase in antigen‐specific CD4 + regulatory cells CD4 + CD25 + CTLA‐4 + with suppressive characteristics was observed .…”
Section: Discussionmentioning
confidence: 93%
“…We also showed that infection resolution induced marked changes in the CD4 + T cell transcriptome which is characterised by an immune regulatory signature. This confirms findings from cellular and molecular studies in the field showing the induction of regulatory molecules in CD4 + T cells during malaria 251,258 . It further suggests that not just one or two, but a whole suite of regulatory markers are induced early in infection, identifying an opportunity to intervene at an earlier timer point to protect against immune suppression.…”
Section: Discussionsupporting
confidence: 89%
“…IL-10 is important for limiting immune pathology caused by proinflammatory, anti-parasitic immune responses 37 . Tr1 cells are a major source of this cytokine in parasitic infections 37,42,155 , and PD1, CTLA4, TIM3, and LAG3 are also known to regulate antigen-specific T cell responses and can be markers of cellular exhaustion in infectious diseases, including malaria 233,239,[250][251][252] . We also observed increased expression of several genes associated with cytolytic activities after drug treatment, including granzymes A, B, H and K, and perforin, as has previously been reported for a subset of cytolytic CD38 + CD4 + T cells in CHMI studies that were positively associated with increased control of parasite growth 253 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations